Oferta do ensino fundamental em São Paulo: um novo modelo - Adrião, Theresa [UNESP] (Centro de Estudos Educação e Sociedade (CEDES), 2008)
Este trabalho propõe-se a refletir sobre o conteúdo e as implicações, para a oferta da educação básica, de duas das principais medidas que sustentaram a reforma da educação paulista implantada pelo primeiro governo de Mario Covas (1995-1998). São elas: a reorganização das escolas da rede estadual e a política de municipalização do ensino fundamental mediante a adoção de convênios.

This paper is aimed at fostering a reflection about the contents of two educational measures and their implications for basic education supply in the state of São Paulo. They are the reorganization of schools within the state educational system and the policy of municipalization of elementary education through the adoption of partnerships, two of the main measures that supported the educational reform implemented by governor Mário Covas between 1995 and 1998.
Elementary educaction supply in São Paulo: a new model
Keywords: Descentralização; Municipalização; Reforma educacional; Gestão educacional; Decentralization; Municipalization; Educational reform; Educational administration